How Speakers Orient to the Notable Absence of Talk: A Conversation Analytic Perspective on Silence in Psychodynamic Therapy - Knol, A. S. L.; Koole, Tom; Desmet, Mattias; Vanheule, Stijn; Huiskes, Mike (Frontiers in Psychology, 2020)
Silence has gained a prominent role in the field of psychotherapy because of its potential to facilitate a plethora of therapeutically beneficial processes within patients’ inner dynamics. This study examined the phenomenon from a conversation analytical perspective in order to investigate how silence emerges as an interactional accomplishment and how it attains interactional meaning by the speakers’ adjacent turns. We restricted our attention to one particular sequential context in which a patient’s turn comes to a point of possible completion and receives a continuer by the therapist upon which a substantial silence follows. The data collection consisted of 74 instances of such post-continuer silences. The analysis revealed that silence (1) can retroactively become part of a topic closure sequence, (2) can become shaped as an intra-topic silence and (3) can be explicitly characterized as an activity in itself that is relevant for the therapy in process. Only in this last case, the absence of talk is actually treated as disruptive to the ongoing talk. Although silence is often seen as a therapeutic instrument that can be implemented intentionally and purposefully, our analysis demonstrated how it is co-constructed by speakers and indexically obtains meaning by adjacent turns of talk. In the ensuing turns, silence indeed shows to facilitate access to the patient’s subjective experience at unconscious levels.